Pemanfaatan Limbah Ampas Kelapa Menjadi Pupuk Organik di SMA Yadika 5 Jakarta Barat - Sitorus, Tosty Maylangi; Kaidah, Sri; Purba, Ari Pranata Primisa; Sahaq, Anang Baharuddin; Yahya, Agung Kurnia; Miftahurrahmah, Miftahurrahmah (Universitas Nahdlatul Ulama Sumatera Utara, 2025)
SMA Yadika 5 has one of the goals, namely